Religion As Subaltern Agency - Gregory Ajima Onah; Thomas Eneji Ogar; Ibiang O. Okoi (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
This study examines the role of religion in facilitating the liberation of marginalized and oppressed groups, sometimes referred to as the subaltern. The word